Does silver diammine fluoride concentration influence on bonding to carious dentinal lesions in primary teeth? - Scherer, M. M.; Lunkes, N. F.; Soares, I. P.M. [UNESP]; de Oliveira, C. A. [UNESP]; Imparato, J. C.P.; Hebling, J. [UNESP]; Lenzi, T. L. (Springer Nature, 2022)
Purpose: This in vitro study evaluated the microshear bond strength (μSBS) of a universal adhesive after silver diammine fluoride (SDF) application at different concentrations on carious dentinal lesions in primary teeth. Methods: Flat dentin carious-induced surfaces from 40 primary molars were randomly assigned to four experimental groups: without SDF treatment (control), 12% SDF, 30% SDF, or 38% SDF application. After 14 days of storage in artificial saliva at 37 °C, a universal adhesive system (Scotchbond Universal, 3 M ESPE) was applied in the etch-and-rinse mode and resin composite cylinders were built (0.72 mm2). After 24 h of water storage, the μSBS test was performed and the failure mode was determined. Data were analysed using one-way ANOVA and Tukey’s post hoc tests (α = 0.05). Results: The application of 38% SDF resulted in higher μSBS mean than control and use of 12% SDF (p = 0.006). No significant differences were observed among control, 12% SDF, and 30% SDF. All specimens tested showed adhesive/mixed failure. Conclusion: The use of SDF does not jeopardise the bonding of a universal adhesive applied in the etch-and-rinse mode to carious dentinal lesions in primary teeth, irrespective of the product concentration.
Keywords: Cariostatic agents; Deciduous; Dental caries; Tensile strength; Tooth